Analysis Of Santri Cleanliness Violation Patterns Using Apriori Algorithm Approach At Salafiyah Syafi'iyah Boarding School - Ilham Rafi Jawara; Zaehol Fatah; Akhlis Munazilin (Jurnal Riset Informatika, 2025)
Islamic boarding schools (pondok pesantren) are religious-based educational institutions that emphasize not only Islamic teachings but also the development of character and student discipline, particularly in maintaining environmental cleanliness. However, managing cleanliness often poses a challenge due to low student awareness and the suboptimal implementation of sanitation systems. This study aims to identify behavioral patterns related to student cleanliness through a data mining approach utilizing the Apriori algorithm. This method enables the analysis of students’ habitual behaviors using collected data to uncover hidden patterns related to cleanliness violations. The research was conducted at Salafiyah Syafi'iyah Sukorejo Islamic Boarding School and provides valuable insights for pesantren administrators to design more effective, data-driven cleanliness management strategies. The findings are also expected to enhance student awareness of cleanliness as an essential aspect of Islamic values. Overall, the results serve as a foundation for strategic decision-making to foster a healthy, clean, and supportive environment conducive to optimal learning in Islamic boarding schools.